PENGARUH PELAKSANAAN PENDIDIKAN DAN PELATIHAN TERHADAP PENINGKATAN KINERJA PEGAWAI PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN PROVINSI SULAWESI BARAT - Sri Hamdyani (AkMen JURNAL ILMIAH, 2014)
This study aimed to determine the effect of the implementation of education and training on employee performance improvement at the Supreme Audit Agency Representative Sulawesi WEST methods used are simple regression analysis method, namely the method is used as a measuring tool in the statistical results of the discussion, and analyzed to provide argumentation clear on the issues that dihadapi.Metode quantitative measure employee performance improvement . The result of the discussion Education and training have a positive relationship with employee performance . The more education and training is done then further improve the performance of employees . Education and training effect for 58.03 % of the increase in employee performance BPK Representative West Sulawesi province while the remaining 41.97% is influenced by other factors such as salary, benefits and incentive activities